Characterizing the weather band variability of the Texas shelf current - Nwankwo, Uchenna C.; DiMarco, Steven F.; Nowak, Heather M.; Whilden, Kerri; Buckingham, Brian; Walpert, John; Knap, Anthony H. (Frontiers in Marine Science, 2023)
Considering the benefits of understanding the circulation patterns of the shelf, it is not surprising that there are numerous studies of the Texas Shelf circulation patterns. Given that previous studies were focused on the low frequency variability of the circulation which is upcoast (northeast flow) in the summer and downcoast (southwest flow) especially on the inner shelf in the non-summer seasons, this study investigates the weather band (2-15 days) variability of the Texas Shelf near surface circulation pattern. Current meter data at 1.5 m below the seas surface from the inner, mid and outer shelves were analyzed. This study demonstrated that there are high frequency current reversals within the weather band in each season. From the estimated persistence of the currents during reversals, the inner and mid shelf currents are predominantly downcoast in the non-summer seasons and upcoast in the summer season while the outer shelf currents are mostly upcoast all year round. The Wavelets analysis of the currents revealed that most of the variabilities on the inner and mid shelf regions were within the 8-15 days band while on the outer shelf the dominant variability was within the 3-8 days band. From the cross-spectra analysis of both the currents and wind data, it was determined that the influence of the wind was more dominant on the inner and mid shelf regions at the 8-15 days band than on the outer shelf where the contribution of the wind is prevalent at the 2-4 days band.